2013
DOI: 10.1088/0264-9381/30/16/165006
|View full text |Cite
|
Sign up to set email alerts
|

Brane-world cosmic strings revive the cosmological constant

Abstract: We obtain the static and cylindrically symmetric vacuum solutions of Einstein's field equations in the framework of the brane-world model where the matter is localized on the brane by means of a confining potential. Considering a constant curvature bulk, one interesting solution is studied, which is similar to the cosmic string solution in a de Sitter spacetime which confirms the idea that the extra geometrical terms in the gravitational field equations on the brane may be the origin of a positive cosmological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…¯L would be identified as an induced magnetic moment tensor 10 . This coupling is a new quantum potential, for relativistic spinless charged particles on the brane, which is remarkably independent of the curvature and torsion.…”
Section: Angular Momentum Of the Normal Coordinates And Induced Zeema...mentioning
confidence: 99%
See 2 more Smart Citations
“…¯L would be identified as an induced magnetic moment tensor 10 . This coupling is a new quantum potential, for relativistic spinless charged particles on the brane, which is remarkably independent of the curvature and torsion.…”
Section: Angular Momentum Of the Normal Coordinates And Induced Zeema...mentioning
confidence: 99%
“…Moreover, assuming that the matter confined in the four-dimensional brane is the only source for the Einstein field equations on the bulk, one can show that the extrinsic curvatures are another source for the Einstein field equations on the brane [2,[4][5][6][7][8]. The presence of this extra source has been proposed as a possible x-cold dark matter [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the detection of cosmic strings could be a possible way to verify the inflationary paradigm, providing an interesting testing ground into string theory by probing the braneworld scenario before the inflationary phase [29,30,31,32]. Many other publications have investigated the effects of braneworld gravity on the physics of cosmic strings [34,35,36,37,38,39]. Specifically in [39], the authors have studied the consequences of the braneworld modified gravity on the cosmic string phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, strings quantization has been studied in the framework of a AdS 5 × S 5 [4]. The study of the cosmological implications of topological defects has become an area of sustained interest [5].…”
Section: Introductionmentioning
confidence: 99%